The TSC2 c.2742+5G>A variant causes variable splicing changes and clinical manifestations in a family with tuberous sclerosis complex - Fan, Kuan; Guo, Yi; Song, Zhi; Yuan, Lamei; Zheng, Wen; Hu, Xiao; Gong, Lina; Deng, Hao (Frontiers in Molecular Neuroscience, 2023)
Tuberous sclerosis complex (TSC) is a genetic, variably expressed, multisystem disease characterized by benign tumors. It is caused by pathogenic variants of the TSC complex subunit 1 gene (TSC1) and the TSC complex subunit 2 gene (TSC2). Genetic testing allows for early diagnosis, genetic counseling, and improved outcomes, but it did not identify a pathogenic variant in up to 25% of all TSC patients. This article reports the results of a study of a Han-Chinese family with TSC-afflicted members. These members had variable clinical manifestations including rare bilateral cerebellar ataxia symptom. Whole exome sequencing, Sanger sequencing, and segregation analysis identified the TSC2 gene c.2742+5G>A variant as a genetic cause. The splicing analysis results obtained from six prediction tools, minigene assay, and patients’ lymphocyte mRNA were compared, and quantitative reverse transcription PCR was performed to confirm the pathogenicity of this variant. This variant inactivated the donor splice site, a cryptic non-canonical splice site was used for different splicing changes in two affected subjects, and the resulting mutant mRNA may be degraded by nonsense-mediated decay. These results show that prediction tools and minigene assay may have defects in predicting cryptic splice sites. Three-year follow-up results suggest the effects of a combined treatment of sirolimus and anti-epilepsy drugs for TSC-related epilepsy and cognitive deficits. These findings expand the phenotypic and genetic spectrum of TSC and may contribute to its diagnosis and treatment, as well as a better understanding of the splicing mechanism.